Nature of the problem of hegel - Razok, Ibrahim; Naser, Alaa (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Find sheds light on the problem perhaps more importantly, the total problems that we find in the history of philosophy , and is not a problem of nature Our research is trying to explore the meaning of the nature of the Beginnings, As we will try to, In this research dealt with the nature of the problem of the two sides Systematic and cognitive To find out the key points of the nature of the problem when the philosophers of the seventeenth century To try to adjust the nature of the problem in its historical context As we will try in this research shed light on the relationship between nature and other problems In the philosophy of Hegel, such as the relationship , for example, between nature and logic, nature and absolute idea. Is Hegel was able to solve the problem of nature and its relationship with the various aspects of his philosophy ؟ Or is it Al this problem and do so by him Kant There is also in our many other problems discussed by Hegel with nature problem.